Management of Forearm Fracture in Adolescence - Tania F; Siswanto BA; Rusdianto IA; Pramantha B (Cermin Dunia Kedokteran, 2021)
Forearm shaft fracture usually occurs because of indirect trauma, especially when a child protect him/herself by an out-stretched upper-extremity during fall. CRIF with TENS can be the treatment of choice in adolescents with simple forearm fracture especially with concern to return to pre-injury function and physical appearance. The patient had a history of fractures of both bones of the right forearm 3 months before and the fractures were fixated using TENS, the satisfying outcomes (faster return to his initial ability to play sport, without any dysfunction, no visible big scar) was the reason we recommended the using of TENS to fixate the current fractures.Fraktur tulang lengan bawah biasanya terjadi akibat trauma tak langsung, umumnya jika sseseorang berusaha menahan tubuhnya saat terjatuh. Teknik CRIF dengan TENS merupakan salah satu yang terpilih untuk tatalaksana fraktur lengan bawah sederhana. Dilaporkan seroang anak laki-laki 12 tahun dengan fraktur kedua lengan bawah yang ditatalaksana dengan TENS dengan hasil memuaskan.